Shopping Mall Motorcycle Parking Lot Mobile Application - Ooi, Kean Hong (Journal of International Conference Proceedings, 2024)
The purpose of this study is to address the current payment method for shopping mall motorcycle parking lot in Penang, Malaysia. The study aims to provide a shopping mall motorcycle parking mobile application for motorcyclists to pay the parking fee at shopping mall motorcycle parking lot in Penang Island which is commonly available at one designated location such as in the basement level or outdoor area. M A R C is a shopping mall motorcycle parking lot mobile application that is the proposed solution that provide an alternative payment method for motorcyclists by introducing a payment method for motorcyclists through the mobile application. The mobile application developed serve to provide additional information about the shopping mall motorcycle parking lot as there is a lack of user-friendly motorcyclist mobile application available in the market for Malaysian motorcyclists. Hence, the mobile application developed using Flutter should ease the payment process with the new alternative mobile application payment method and provide motorcyclists with the necessary information regarding the selected shopping mall motorcycle parking lot in Penang Island.